typo/graphic days 8 - Panayides, Angelos (My University, 2024)
Posters are an effective medium for conveying messages and storytelling. They are visual art pieces encompassing paintings and illustrations dating back to the 19th and 20th centuries and are widely recognized as culturally significant artifacts. The UDA’s prestigious annual design competition allows participants to exhibit their finest posters, which the UDA will preserve as historical artifacts. Participants are encouraged to submit their top commercial posters for clients, experimental posters for their creative endeavors, and environmental awareness posters to advocate for environmental preservation.
Keywords: exhibition catalogue